Self‐emulsifying drug delivery system of (R)‐α‐lipoic acid to improve its stability and oral absorption. (23rd April 2021) - Banik, Sujan; Halder, Shimul; Sato, Hideyuki; Onoue, Satomi
Abstract: The present study was designed to develop a self‐emulsifying drug delivery system (SEDDS) of ( R )‐ α ‐lipoic acid (RLA) to improve the physicochemical and nutraceutical properties of RLA. RLA/SEDDS was prepared using medium‐chain triglycerides, Tween 80, and polyethylene glycol 400 as oil, surfactant, and co‐surfactant, respectively. The preferable composition of SEDDS was selected according to a pseudo‐ternary phase diagram for improved emulsification properties, and its physicochemical and pharmacokinetic properties were evaluated. RLA/SEDDS showed the immediate formation of fine micelles with a mean droplet size of approximately 260 nm when introduced into aqueous media. In simulated gastric fluid, this system could significantly improve the dissolution behavior of RLA and prevent the degradation of RLA, possibly due to the encapsulation of RLA into the emulsion structure. Following the oral administration of RLA/SEDDS (10 mg RLA/kg) in rats, systemic exposure to RLA and dihydrolipoic acid (DHLA), a reduced form of RLA, increased by 7‐ and 3‐fold, respectively. The improved dissolution and gastric stability of RLA could contribute to enhancing systemic exposure to RLA and DHLA after oral administration. From these findings, RLA/SEDDS might be an efficacious dosage option for improving the oral bioavailability as well as nutraceutical properties of RLA. Abstract : Self‐emulsifying drug delivery system of (R)‐α‐lipoic acid significantly reduced the degradation of RLA under acidic conditions and improved its oral absorption behavior, possibly due to the encapsulation of RLA into the emulsion structure. The SEDDS approach might be one of the viable options for improving the pharmacokinetic behavior of RLA and its stability under acidic conditions, possibly leading to enhancement of the nutraceutical properties.